Early thermal aging detection in tin based perovskite solar cell - H. Amanati Manbar; Z. Hosseini; T. Ghanbari; E. Moshksar; M. Khodapanah (Heliyon, 2022)
Tin-based perovskite solar cells (T-PSCs) are introduced as the next generation of valid and environment-friendly photovoltaic (PV) cells for near-future commercialization. However, there are some issues limiting T-PSCs including their instability, low efficiency, and use of toxic processing solvents. Among all these barriers, instability and early aging under thermal stress conditions are considered as significant challenges to the development of the T-PSCs. In this study, the impact of different temperature levels on the performance of a T-PSC is investigated over time. It is observed that early degradation of the device occurs at higher temperatures. For timely detection of the early aging, an accurate adaptive estimation of the series resistance is obtained in the equivalent single-diode circuit model of the T-PSC. It is shown that the trend of changes in the series resistance is a reliable indication of the aging process in the T-PSC. Finally, a mathematical index is derived for early aging detection based on the relative variation of the gradient from its minimum value in the linear regression analysis. The proposed approach could be utilized for timely detection of early aging conditions and protection of the device from permanent damage.